ANALISIS KETERPILIHAN MISNA WALIA SETRI SEBAGAI KEPALA DESA PULAU TONGAH SIBERAKUN KECAMATAN BENAI - Ryanda Adlis; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The winning of the woman village head is a form of woman existence in political world. Misna Walia Setri is considered as the manifestation of woman’s involvement in politic. During the direct village head election in Kuantan Singingi Regency in 2015, among the 137 candidate running for the position, Misna was the one and only woman candidate. She successfully managed 43% of the voters in her region supported for her. This favorable situation let her defeated other candidate and she was elected as the woman head village. This research attempts to analyze the winning of Misna as the head village of Pulau Tongah Siberakun Kecamatan Benai. This research uses descriptive-qualitative method. Data are collected through interview and documentation. The found-out of this research indicates that people perception toward the women-led figure is getting more open and positive. Then, writer also found out another factor that contributed to Misna’s winning such as internal factors that are the social and economic capital as well as external factor that are voter behavior, political capital, gender equality issues, and money politic.Keywords: Village Chief Election, Voting Behavior, Behavior Choosing